تنفيذ أحكام القضاء الإداري الصاردة ضد السلطة التنفيذية في المملكة العربية السعودية /‏ - آل يحيى، سلطان حسن سلطان (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
This study deals with the issue of executing the decision of administrative court issued against the executive authority in Saudi Arabia. The study examines the obstructions and their causes that may be faced in executing such decision. The study also identifies methods and means that may be referred to by executive authority in this matter. It highlights judicial and non-judicial methods and means that can be applied in overcoming the behaviour of the executive authority in abstaining from execution of the decision which of course contrary to the established principle. The legislative and judicial systems of the Kingdom of Saudi Arabia are based on Islamic law. Nevertheless, Board of Grievance of the Kingdom adopts the current administrative court practice with respect to the execution of the decision which is clearly contrary to the practice of the Grievance system in Islam. Thus the study also examines the grievance system in Islam to highlight the similarities and differences with administrative court system of the Kingdom with respect to the execution of the decision. The methodology of this study is mainly based on inductive and descriptive analysis methods. It also conducts some interview with specialized person in the field of administrative court system. The study finds that the main reason the decision of administrative court cannot be executed against the executive authority because the adoption of the principle non interference of administrative court in executing its decision. The study also suggests some recommendation with respect to the execution of the decision of administrative court and proposes some mechanism with respect to the execution of the decision issued by the Board of Grievance.